TINGKAT KUALITAS KESEHATAN LINGKUNGAN RUMAH HUNI DAN PERMUKIMAN DI KECAMATAN SENAPELAN KOTA PEKANBARU - Suryani Suryani (EcoNews, 2019)
The development of residential environment in urban areas is inseparable from the rapid growth of urban population both because of the growth factor of the urban population itself and because of the urbanization factor. Pekanbaru is a city with rapid development. However, on the other hand, the rapid development of Pekanbaru City has an impact on population growth and densely populated settlements and many residents of Pekanbaru who have low economy do not have a permanent residence so that people do not pay attention to occupancy in accordance with health standards. The purpose of this study is to determine the level of quality of environmental health of residential houses and settlements in Jalan Meranti Village Kampung Baru Senapelan District Pekanbaru City. Data analysis in this research use descriptive analysis. The level of quality of environmental health of residential houses and settlements can be known from the results of the parameter index of each indicator and weighting of each indicator usedbaik it is for the indicator of environmental health of residential houses and settlements. The results of this study indicate the level of environmental health quality of houses and settlements in Jalan Meranti Village Kampung Baru Senapelan District Pekanbaru city is bad from some index parameters